2014
DOI: 10.1101/gad.240820.114
|View full text |Cite
|
Sign up to set email alerts
|

MuLV-related endogenous retroviral elements and Flt3 participate in aberrant end-joining events that promote B-cell leukemogenesis

Abstract: During V(D)J recombination of immunoglobulin genes, p53 and nonhomologous end-joining (NHEJ) suppress aberrant rejoining of DNA double-strand breaks induced by recombinase-activating genes (Rags)-1/2, thus maintaining genomic stability and limiting malignant transformation during B-cell development. However, Rag deficiency does not prevent B-cell leukemogenesis in p53/NHEJ mutant mice, revealing that p53 and NHEJ also suppress Rag-independent mechanisms of B-cell leukemogenesis. Using several cytogenomic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Furthermore, cytokines serve critical roles in early B cell development and function. Flt3 was the most highly enriched cytokineencoding gene in the TM cells [log 2 Fc (fold change) = −5.39 and FDR-adjusted q = 4.20 × 10 −9 ], in line with our previous finding that somatic Flt3 mutation causes activation and aberrant expression in TM B-ALL (40). Among other cytokine-encoding genes overexpressed in TM relative to DM B-ALL, we focused by Tnfsf11 (Rankl) encoding RANKL (log 2 Fc = −3.46 and FDR-adjusted q = 4.81 × 10 −4 ), due to its critical role in bone remodeling.…”
Section: Rankl Expression In the Tm Mouse Model Of Early B-allsupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, cytokines serve critical roles in early B cell development and function. Flt3 was the most highly enriched cytokineencoding gene in the TM cells [log 2 Fc (fold change) = −5.39 and FDR-adjusted q = 4.20 × 10 −9 ], in line with our previous finding that somatic Flt3 mutation causes activation and aberrant expression in TM B-ALL (40). Among other cytokine-encoding genes overexpressed in TM relative to DM B-ALL, we focused by Tnfsf11 (Rankl) encoding RANKL (log 2 Fc = −3.46 and FDR-adjusted q = 4.81 × 10 −4 ), due to its critical role in bone remodeling.…”
Section: Rankl Expression In the Tm Mouse Model Of Early B-allsupporting
confidence: 84%
“…In previous studies, we identified an ectopically expressed Flt3 mutation that promotes early B cell leukemogenesis in triple mutant (TM) mice (40). The TM mice harbor mutations that arrest B cell development (Rag2 −/− ) and disrupt DNA repair (Prkdc scid/scid ) and DNA damage checkpoints (p53 −/− ) (41).…”
Section: Rankl Expression In the Tm Mouse Model Of Early B-allmentioning
confidence: 99%
See 1 more Smart Citation
“…CNS BCP-ALL was observed in mice triple mutant for RAG1/2, the non-homologous end joining repair and TP53 (Gladdy et al, 2003). Further molecular studies of this unique mouse model revealed a molecular rearrangement that results in the activation of FLT3 (Johnson et al, 2014). They further showed that this activation was essential for the CNS phenotype.…”
Section: How Do Leukaemic Cells Survive In the Cns? Interactions Withmentioning
confidence: 90%
“…Animal models with genetic mutations are commonly used to determine gene function. Numerous methods for generating mutations, including X-rays, chemical mutagenesis, retroviral transfection, and transgenic technology, have been used in gene function research 11 12 13 14 ; however, these methods do not produce stable expression, frequently affect multiple genes or lead to chromosomal rearrangements, and cannot provide molecular markers to allow collection of mutation information 12 .…”
mentioning
confidence: 99%